Hidden lives, public personae : women and civic life in the Roman West - Hemelrijk, Emily (Oxford University Press, 2015)
This study discusses women's participation in civic life in the cities of Italy and the Latin-speaking provinces of the Roman Empire from the late first century BC to the late third century AD (roughly the Roman Principate). Excluding empresses and other women of the imperial family, it focuses on the civic roles of non-imperial women in Italian and provincial towns on the basis of a corpus of approximately 1,400 inscriptions and, to a lesser extent, honorific portrait statues